A nucleic acid-directed, red light-induced chemical reaction - Fülöp, Annabelle; Peng, Xiaohua; Greenberg, Marc M.; Mokhir, Andriy (Chemical communications, 2010)
The first nucleic acid-directed catalytic photochemical reaction that is induced by nontoxic red light was developed. This reaction is fast, high yielding, sequence specific, and enables one to functionalize an oligonucleotide.
Gesehen am 17.07.2023